Optimalisasi Dividen Pada Perusahaan Yang GO Publik di Bursa Efek Indonesia - Sukma Irdiana (Ecobuss, 2018)
The functions of finance are investment decisions, funding decisions, and dividend policies. Dividend policy is a decision on profit sharing from the company. Dividend policy is a difficult decision for the company. Because the company must be able to share dividends in accordance with the expectations of investors. Investors expect profits as a result of their investments. On the other hand dividend distribution is expected not to affect the survival of the company. Due to the high dividend payout is less favored by management because it will reduce management utility caused by the smaller funds that are within the scope of management control. The purpose of this study is to determine the effect of solvency, liquidity, profitability, growth rate, and investment opportunities affect the company dividend policy in Indonesia Stock Exchange 2010-2015 period, either partially or simultaneously. Sample selection method used is purposive sampling and analysis model used is multiple linear regression analysis. The results showed that partially DER and IOS significantly affected the House. While CR, ROA and Assets Growth have no significant effect on DPR. Simultaneously DER, CR, ROA, Assets Growth and IOS simultaneously affect the House. The coefficient of Determination (R Square) of 21.2% and the rest of 78.8% influenced by other variables that have not been studied in this study. Keywords : DER, CR, ROA, Assets Growth dan IOS